2016
DOI: 10.7554/elife.21126
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the C. elegans egg-laying behavior circuit is controlled by competing activation and feedback inhibition

Abstract: Like many behaviors, Caenorhabditis elegans egg laying alternates between inactive and active states. To understand how the underlying neural circuit turns the behavior on and off, we optically recorded circuit activity in behaving animals while manipulating circuit function using mutations, optogenetics, and drugs. In the active state, the circuit shows rhythmic activity phased with the body bends of locomotion. The serotonergic HSN command neurons initiate the active state, but accumulation of unlaid eggs al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
201
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(218 citation statements)
references
References 59 publications
16
201
1
Order By: Relevance
“…Prior work suggested that the neurosecretory uv1 cells may terminate egg-laying, perhaps by sensing the passage of eggs through the vulva [18,29]. Our work supports this model and extends it in several important aspects.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Prior work suggested that the neurosecretory uv1 cells may terminate egg-laying, perhaps by sensing the passage of eggs through the vulva [18,29]. Our work supports this model and extends it in several important aspects.…”
Section: Discussionsupporting
confidence: 85%
“…Prolonged inhibition of the uv1 cells in adult animals significantly reduces the length of the inactive phase of egg-laying. A recent study found that calcium transients occur in uv1 cells immediately following egg-laying events during an active phase [18], suggesting that repetitive stimulation of uv1 cells may be required for inhibition of egg-laying. We speculate that each egg-laying event may trigger release from the uv1 cells, ultimately leading to local increases in peptide levels sufficient to terminate the active phase and delay re-entry into the subsequent active phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium transients in VC neurons, particularly VC4 and 5, are temporally associated with egg laying events. 42 Thus, we analyzed egg laying behavior to determine if behavioral differences could be used to screen for neuroprotective treatments. Consistent with a recent report of silencing VC neuron activity that did not alter the number of unlaid eggs, 43 we found no difference in the average number of unlaid eggs on D1 or D3 of adulthood for SC_APP and WT worms (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…42 We first tested whether VC neuron ablation by cell-specific expression of human Casp1 (ICE) impaired swimming. As similar results were found for head bend rate and swim speed, only swim speed is reported.…”
Section: Resultsmentioning
confidence: 99%